Using mobile technology to track wine tourists - Gemma K. Lewis; Anne Hardy; Martha P. Wells; Fiona L. Kerslake (Annals of Tourism Research Empirical Insights, 2021)
Understanding how tourists behave when visiting a destination is invaluable information for businesses. Despite the prevalence of wine tourism and its economic contribution, prior research has typically used surveys which produce coarse data. In this study, we used an innovative mobile phone app with integrated survey and Global Navigation Satellite System (GNSS) technology to examine the movements of wine tourists within an Australian wine region. This method offers a finer grained spatio-temporal approach for understanding wine tourist behaviour and has implications for the marketing and planning that occurs within wine regions.